EVALUATION OF THE SHAPE AND SIZE OF THE SELLA TURCICA IN X-RAYS CEPHALOMETRIC OF PATIENTS ATTENDED IN THE DENTISTRY CLINIC OF THE UNIVERSITY SAN MARTIN DE PORRES 2010-2014. - Vásquez Santa-Cruz, Luis (2016)
Objective: The aim of the present study was to assess the shape and size of the sella turcica in cephalometric radiographs of patientsattending the Specialized Clinic in dentistry of the San Martin de Porres University during the years 2010-2014. Materials andmethods: 180 lateral cephalometric radiographs were evaluated; 90 males and 90 females between 09-30 years of age. Results: Theresults showed that sellas turcicas with different shapes depend on gender and malocclusions, round sellas turcicas in 73.3% of thecases, oval shape in 11.7% and flat in 15% of the sample (p = 0.596). In class III antero-posterior dimension was found to be decreased(p =. 007). Conclusions: This study showed significant differences regarding the skeletal patterns and size of the sellas turcicas,finding a greater predominance of round shape. At the level of the midline in the class dimension III showed to be decreased. KIRU.2016;13(2):138-143.